2018
DOI: 10.4236/jgis.2018.106035
|View full text |Cite
|
Sign up to set email alerts
|

Flood Risk Code Mapping Using Multi Criteria Assessment

Abstract: Flash flood is a dangers natural disaster causes lots of structure damage, traffic collapse, economic defects and human life loss. An efficient way to reduce its effects is preparing flash flood mapping to identify zones at risk due to flood. Flash flood mapping is a powerful tool for urban planners, traffic and infrastructure engineers, emergency and rescue services. This article proposes an approach utilizes remote sensing (RS) and geographic information system (GIS) to prepare flood risk code (FRC) map for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These basins have low values of the shape factor, ranging from 2.08 (B32) to 5.29 (B40) and steep slopes, ranging from 10.92 (B35) to 36.16% (B15), which accordingly result in high flow velocities, low infiltration, and higher flood peaks (Ogarekpe et al 2020). Moreover, the curve number for these basins is high, (Khalil 2018). The basins with the highest hazard degree (very high) are basins B33 and B42.…”
Section: Flood Hazard Assessmentmentioning
confidence: 99%
“…These basins have low values of the shape factor, ranging from 2.08 (B32) to 5.29 (B40) and steep slopes, ranging from 10.92 (B35) to 36.16% (B15), which accordingly result in high flow velocities, low infiltration, and higher flood peaks (Ogarekpe et al 2020). Moreover, the curve number for these basins is high, (Khalil 2018). The basins with the highest hazard degree (very high) are basins B33 and B42.…”
Section: Flood Hazard Assessmentmentioning
confidence: 99%
“…Hydrology analysis include estimation of rainfall depth at a specific return period, determination of catchment morphometric parameters and estimation of runoff depth and runoff volume. The details of hydrology analysis for the study area can be found in [34].…”
Section: -3-2 Hydrology Analysismentioning
confidence: 99%
“…The results of volume and area of the polygon features, as well as the code values obtained from the SDM, were utilized to provide a collection of water depth estimates and to synthesize maps from the predicted floodplains. The equation used in computing the flood water depth (FWD) is as follows: where C is the code value (1,-1, or 0); V and Ar are the volume and surface area of the predicted floodplains from SDM, respectively (Cham et al 2016;Khalil 2018).…”
Section: Developing Sdmmentioning
confidence: 99%